Os jogos digitais no contexto clínico Junguiano - Polcino, Marcos Daniel Grassmann (2019)
Taking into account the increasing presence of digital games in contemporary everyday life and the potential it has to impact the individuals that consume it, this work intends to identify the ways in which digital games become present in Jungian therapy. To this end, we explore the conceptualization of digital games, its aspects that are related to games with rules, its narrative characteristics, as well as a brief note on the question of dependence on digital games. The methodology used was qualitative, through semi-structured interviews with eight Jungian therapists that work with child therapy. The data obtained was organized in two thematic groups. In the first group, the context in which the therapy occurs and in the second group the forms of clinical work adopted by the participants were emphasized considering also the influence of this entourage on the clinic. It was possible to understand the digital games as elicitor of the symbolic function to the psyche as well as the fact that this symbolic potential acts on patients, therapists and, also, in the entire social context that surrounds the analytical encounter